PELATIHAN DAN PENDAMPINGAN PRODUKTIVITAS PERTANIAN MELALUI HIDROPONIK DI DESA BRONJONG - Muchamad Suradji; Retno Nuzilatus Shoimah; Namirah Arrasyidah; Gilang Setyo Pratomo; Fajrur Romadhoni (LPPM Universitas Islam Darul 'Ulum Lamongan, 2024)
This service aims to provide training and community service for agricultural productivity through hydrophonics in Bronjong Village. This dedication is intended to maximize assets in the form of community home gardens to function as productive land with hydrophonic technology. This service uses an Asset Based Community Development (ABCD) approach. The ABCD method has five stages for carrying out the mentoring research process, including: Discovery (Study), Dream (Dream), Design (procedure), Define (Consolidation of Goals), and Destiny (Self Determination). The results of the service carried out by the service and partners in increasing agricultural productivity through the hydrophonic program. This program is important, because it is in line with village programs, one of which is making villages green by empowering people to plant plants in their yards. House yards that are not used become assets that can be used for more productive things, such as hydrophonics. Utilizing this asset is a solution to limited land for planting. Apart from that, the benefits provided by hydrophonic products can later be used for daily needs and can also be used as additional income by selling the crops. In the future, hydrophonics will become one of the icons of a green village if it is implemented en masse by the people of Bronjong village. So, in the future, the farmers of Bronjong Village will inspire smart, sustainable and adaptive farmers.